2011
DOI: 10.1186/1741-7015-9-82
|View full text |Cite
|
Sign up to set email alerts
|

MIA is a potential biomarker for tumour load in neurofibromatosis type 1

Abstract: BackgroundNeurofibromatosis type 1 (NF1) is a frequent genetic disease characterized by multiple benign tumours with increased risk for malignancy. There is currently no biomarker for tumour load in NF1 patients.MethodsIn situ hybridization and quantitative real-time polymerase reaction were applied to investigate expression of cartilage-specific genes in mice bearing conditional inactivation of NF1 in the developing limbs. These mice do not develop tumours but recapitulate aspects of NF1 bone dysplasia, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Recently, two studies identified MIA and ADM as potential NF1 tumor markers in cohorts of 42 and 32 patients, respectively [21,23]. There was also a trend towards correlation between ADM and MPNST, although the MPNST group was too small to show significance (n = 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, two studies identified MIA and ADM as potential NF1 tumor markers in cohorts of 42 and 32 patients, respectively [21,23]. There was also a trend towards correlation between ADM and MPNST, although the MPNST group was too small to show significance (n = 5).…”
Section: Resultsmentioning
confidence: 99%
“…Among such factors, serum levels for midkine and for stem cell factor were found to be significantly increased in a cohort of 39 patients with NF1, although no correlation with tumor load or MPNST was found [20]. Recently, we identified melanoma-inhibitory activity (MIA; also known as cartilage-derived retinoic acid-sensitive protein (CD-RAP)) as a marker for the internal tumor load in a cohort of 42 patients with NF1 [21]. MIA was shown previously to be a biomarker for malignant neuroectotermal tumors [22].…”
Section: Introductionmentioning
confidence: 99%
“…To date, no reliable circulating biomarkers have been validated for nerve sheath tumors although adrenomedullin, MIA, and SOX9 have been suggested for future Page 8 development [9][10][11]. Proteomic analysis of plasma samples from NF and non-NF patients may help identify candidate proteins that correlate with tumor burden.…”
Section: Discussionmentioning
confidence: 99%
“…For histological analysis, ventricular heart biopsies were fixed in buffered 4% paraformaldehyde, dehydrated in subsequent ethanol steps and embedded in paraffin according to standard laboratory procedures (Kolanczyk et al, ). For histological assessment, 5 µm paraffin sections were stained with hematoxylin and eosin (overall tissue organization and cell morphology), sirius red (collagenous material accumulation), and periodic acid‐Schiff reaction (accumulation of carbohydrate macromolecules).…”
Section: Methodsmentioning
confidence: 99%